The Influence of Light and Shadow on Expressiveness in Still Life Painting - Tolibova Umida Davlat qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
ANNOTATION: This article examines the influence of light and shadow on expressiveness in still life painting. It discusses how manipulating light intensity, direction, and shadow shapes can enhance the visual impact and emotional depth of a composition. The study also highlights pedagogical methods for teaching students to observe and apply lighting techniques effectively in their artworks, based on Shovdirov S.A.’s research in visual arts education.